1986
DOI: 10.1111/j.1600-051x.1986.tb01480.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 3 clinical indices for measuring gingivitis

Abstract: A clinical study was conducted among 200 adult males and females to compare the intrusive gingival index (GI) for estimating gingivitis with the nonintrusive and only visually applied papillary-marginal-gingivitis index (PMGI). The GI examinations were performed by a senior examiner with long experience and a junior examiner, while the PMGI was graded by only a senior examiner with long experience. A 4th examiner was included for grading bleeding sites by gentle intrusion at the orifice of the gingival crevice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…When probing is used for bleeding response, the force used, the probe size and probe position are factors that must be taken into consideration (reviewed in Listgarten, 1980). Regarding "bleeding on pressure", Bollmer et al (1986) compared the intrusive gingival index (GI) for estimating gingivitis with a nonintrusive visual index. The results indicated that the methods were similar and the number of bleeding sites per subject did not diminish after manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…When probing is used for bleeding response, the force used, the probe size and probe position are factors that must be taken into consideration (reviewed in Listgarten, 1980). Regarding "bleeding on pressure", Bollmer et al (1986) compared the intrusive gingival index (GI) for estimating gingivitis with a nonintrusive visual index. The results indicated that the methods were similar and the number of bleeding sites per subject did not diminish after manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, it was found that transient bacteremia was induced by toothbrushing in 96 healthy subjects with varying degrees of gingival inflammation; therefore both the degree and extent of gingivitis were assessed (11) . Although the indices used did not include registration of gingival bleeding, changes in color and contour have been observed to precede bleeding on probing (21,22) . GE was divided into 4 subgroups for ease of description and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of gingival indices were developed which rely upon bleeding following "gentle probing'' as an earlier sign of gingivitis such as the Russell's periodontal index (15,16,17) , sulcular bleeding index (SBI), the papillary bleeding index (PBI), the gingival index (GI) (18) and their modifications (19) , as well as the extent & severity index (ESI) (20) . However, the value of bleeding as the most sensitive indicator of gingivitis has been questioned, with some authors noticing that in the early gingivitis, changes in color and contour have been observed to precede bleeding on probing (21,22) . For that reason, a simple modification of the PMA index was used to assess the prevalence of gingivitis for the present group of patients (23,24,25) .…”
Section: Gingival Inflammation Evaluation (Ge and Gs Indices)mentioning
confidence: 99%
“…Varma8 further analyzed the data presented by Bollmer et al 7 Calculating intraclass correlation coefficients, he looked at the distribution of weighted and unweighted kappas. His conclusion was that log-linear models would gradually replace the current use of the kappa statistic.…”
mentioning
confidence: 99%
“…Bollmer et al 7 compared the GI and PMGI for measuring gingivitis. His group presented mean full mouth scores and mean site scores on a severity scale and di-J Periodontol September 1996 chotomous scale for the above indices.…”
mentioning
confidence: 99%